AIP56, an AB toxin secreted by Photobacterium damselae subsp. piscicida, has tropism for myeloid cells - Freitas, Inês Lua; Macedo, Maria Fátima; Oliveira, Liliana; Oliveira, Pedro; do Vale, Ana; dos Santos, Nuno M.S. (Frontiers in Immunology, 2025)
IntroductionThe AB-type toxin AIP56 is a key virulence factor of Photobacterium damselae subsp. piscicida (Phdp), inducing apoptosis in fish immune cells. The discovery of AIP56-like and AIP56-related toxins in diverse organisms, including human-associated Vibrio strains, highlights the evolutionary conservation of this toxin family, suggesting that AIP56 and its homologs may share conserved receptors across species. These toxins have potential for biotechnological applications, such as therapeutic protein delivery and immune modulation.MethodsHerein, the cell specificity of AIP56 for immune cells was characterized. The tropism of AIP56 for cells of the sea bass, mouse and human immune system was analyzed by following toxin internalization by flow cytometry and arrival of the toxin in the cytosol by evaluating the cleavage of NF-kB p65 by western blotting.ResultsOnly a small population of sea bass neutrophils internalized AIP56, indicating that most of the neutrophilic destruction during Phdp infection and/or AIP56 intoxication does not result from the direct action of the toxin. Moreover, the cellular tropism of AIP56 for myeloid cells was observed in the three species, including its preference for macrophages. Further, mouse and human M0 and M2-like macrophages internalized more toxin than M1-like macrophages. Despite the limited interaction of lymphoid cells with AIP56, mouse B1-cells were able to internalize the toxin, possibly due to its myeloid features.ConclusionAIP56 has tropism for sea bass, mouse and human myeloid cells, with greater affinity for macrophages. This points to an evolutionary conservation of its receptor(s) and mechanism of action across species, raising the possibility that AIP56-like and -related toxins may also play a role in pathogenesis. These findings are relevant for both pathogenicity and biomedical contexts.